The national evaluation of Sure Start : does area-based early intervention work? - Belsky, Jay, 1952-; Melhuish, Edward C., 1950-; Barnes, Jacqueline (Policy, 2007)
Following 5 years of systemic research exploring the efficacy and impact of Sure Start Local Programmes, this book pulls together, in a single volume, the results of the extensive National Evaluation of Sure Start (NESS).